PENGARUH JENIS DAN KOMPOSISI PUPUK KANDANG AYAM DAN PUPUK NPK TERHADAP SERAPAN NITROGEN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU DI ENTISOL SIDERA - Prastya, Imam Wahyudi, Baharudin, David (AGROTEKBIS, 2015)
This study aim was to determine the single and the interaction effect of inorganic fertilizers (NPK) and organic fertilizers (chicken manure) on the nitrogen uptake of shallot in entisols Sidera. This study used a Randomized Block design (RBD), which consisted of 9 treatments and replicated three times so that there were 27 experimental units. The treatments consisted of control and two types of fertilizers. The inorganic fertilizers were added at the rate of 150 and 300 kg ha-1, whereas the organic fertilizers at 10t ha -1 and 40 t ha-1. Data was analyzed using analysis of variance to determine the effect between treatments. If the results of analysis of variance showed a significant effect, then it was tested further using 5% honest significant difference (HSD 5%). The results showed that administration of inorganic fertilizer (NPK) at the rate of 300 kg ha-1 significantly increased the nitrogen uptake of the crops while the chicken manure at the rate of 40 t ha-1 very significantly increased the nitrogen uptake and there was no significant interaction between the inorganic and organic fertilizers (NPK) on the nitrogen uptake of the shallot (Allium ascalonicum L.).